Belt, intermediate transfer belt, and image forming device
By designing a tape with specific resistivity and surface resistivity for use in the image forming device, the problem of deterioration of transferability on recording medium with large surface irregularity is solved, and high transferability and reduced whiteness in the concave area is achieved. The effect of the dot.
Patent Information
- Application Number
- CN201911075180.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-24
- Filing Date
- 2019-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2039-11-06
AI Technical Summary
When using the image forming device, the transferability on the recording medium with large surface irregularities may deteriorate, mainly due to the inappropriate volume resistivity and surface resistivity of the tape holding the toner image, and the surface resistance caused by the voltage application time. rate change.
A band is designed, with a volume resistivity of 100V of 5 seconds or more and 12.5 logΩ·cm or less, and a surface resistivity of 100V of 3 seconds or less, and a surface resistivity of 11.0 logΩ/sq and less than or equal to 13.5 logΩ// sq, and the difference between the surface resistivity value of 1 second and 100 seconds is less than 0.5. The surface layer of the tape may contain free polyimide resin and polyamide imide resin, and may contain carbon black.
Even when using a recording medium with large surface irregularity, the belt can achieve high transferability, and the reduction of transferability and the formation of white dots in the concave are avoided.
Smart Images

Figure CN111983908B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a belt, an intermediate transfer belt, and an image forming apparatus. Background Art
[0002] Electrophotographic image forming devices (e.g., copiers, fax machines, and printers) form images by transferring a toner image formed on the surface of an image holding member onto the surface of a recording medium and fixing the toner image onto the recording medium. When transferring the toner image onto the recording medium, a conductive belt such as an intermediate transfer belt is used.
[0003] For example, Japanese Laid-Open Patent Application Publication No. 2010-026432 discloses a multilayer endless belt member for an image forming device, the belt member including a high resistance surface layer capable of holding a toner image. The common logarithm of the surface resistivity of the rear surface of the belt member (i.e., the inner surface of the ring) at 500V for 10 seconds is 9.0 to 12.5log (Ω / sq). The change in the surface resistivity of the front surface of the belt member (i.e., the outer surface of the ring), that is, the common logarithm of the difference between the surface resistivity values of the front surface at 100 seconds and 1 second is 0.5 to 1.50log (Ω / sq) at 100V, and is 0.2log (Ω / sq) or less at 500V. The change in the surface resistivity of the rear surface of the belt member, that is, the common logarithm of the difference between the surface resistivity values of the rear surface at 100 seconds and 1 second is 0.1log (Ω / sq) or less at 100V and 500V.
[0004] Japanese Laid-Open Patent Application Publication No. 2009-139657 discloses a multilayer endless belt member for an image forming device, the belt member including a high resistance surface layer capable of holding a toner image. The common logarithm of the volume resistivity of the belt member is 8.0 logΩ·cm or more and 11.0 logΩ·cm or less. The change in surface resistivity of the front surface (i.e., the outer surface of the ring) of the belt member (i.e., the common logarithm of the difference between the 100-second and 1-second surface resistivity values of the front surface) is greater than the change in surface resistivity of the rear surface (i.e., the inner surface of the ring) of the belt member (i.e., the common logarithm of the difference between the 100-second and 1-second surface resistivity values of the rear surface) by 0.05 log (Ω / sq) or more. Summary of the invention
[0005] When an image is formed on a recording medium having large surface irregularities (e.g., embossed paper) using an image forming apparatus, transferability may deteriorate depending on the volume resistivity and surface resistivity of the belt that holds the toner image, and the difference in surface resistivity due to the amount of time a voltage is applied to the belt.
[0006] Therefore, an object of the present invention is to provide a belt that can achieve high transferability even when using a recording medium with large surface irregularities, compared with a case where the surface resistivity of the outer peripheral surface of the belt at 100 V for 3 seconds is less than 11.0 logΩ / sq or greater than 13.5 logΩ / sq, a case where the volume resistivity of the belt at 100 V for 5 seconds is less than 10.0 logΩ·cm or greater than 12.5 logΩ·cm, or a case where the difference between the surface resistivity values of the outer peripheral surface of the belt at 100 V for 1 second and 100 seconds is greater than 0.5.
[0007] According to a first aspect of the present disclosure, there is provided a belt capable of holding a toner image for an image forming device, the belt comprising a multilayer structure having a surface layer defining an outer peripheral surface of the belt; the volume resistivity of the belt at 100 V for 5 seconds is 10.0 log Ω·cm or more and 12.5 log Ω·cm or less, the volume resistivity at 100 V for 5 seconds being measured after 5 seconds have passed since the start of application of a voltage of 100 V; the surface resistivity of the outer peripheral surface of the belt at 100 V for 3 seconds is greater than 11.0 log Ω·cm; sq and is less than or equal to 13.5logΩ / sq, the 3-second surface resistivity at 100V is measured 3 seconds after the start of application of the 100V voltage; the difference between the 1-second surface resistivity of the outer peripheral surface of the belt at 100V and the 100-second surface resistivity of the outer peripheral surface of the belt at 100V is less than 0.5, the 1-second surface resistivity is measured 1 second after the start of application of the 100V voltage, and the 100-second surface resistivity is measured 100 seconds after the start of application of the 100V voltage.
[0008] According to the second aspect of the present disclosure, the surface layer may include at least one selected from the group consisting of a polyimide resin and a polyamideimide resin.
[0009] According to the third aspect of the present disclosure, the surface layer may be composed of a polyimide resin.
[0010] According to a fourth aspect of the present disclosure, the surface layer may include carbon black.
[0011] According to a fifth aspect of the present disclosure, the amount of carbon black may be 10% by mass or more and 22% by mass or less of the total mass of the surface layer.
[0012] According to the sixth aspect of the present disclosure, the average primary particle size of the carbon black may be 2 nm or more and 20 nm or less.
[0013] According to a seventh aspect of the present disclosure, the total thickness of the tape may be 60 μm or more and 120 μm or less.
[0014] According to an eighth aspect of the present disclosure, the thickness of the surface layer may be 3% or more and 50% or less of the total thickness of the tape.
[0015] According to a ninth aspect of the present disclosure, the multilayer structure may include a base layer disposed adjacent to the surface layer.
[0016] According to a tenth aspect of the present disclosure, there is provided an intermediate transfer belt including the above-mentioned belt.
[0017] According to an eleventh aspect of the present disclosure, there is provided an image forming apparatus including the above-mentioned belt.
[0018] The belts according to the first and ninth aspects of the present disclosure can achieve high transferability even when using a recording medium with large surface irregularities, compared to the case where the surface resistivity of the outer peripheral surface of the belt at 100V for 3 seconds is less than 11.0logΩ / sq or greater than 13.5logΩ / sq, the case where the volume resistivity of the belt at 100V for 5 seconds is less than 10.0logΩ·cm or greater than 12.5logΩ·cm, or the case where the difference between the surface resistivity values of the outer peripheral surface of the belt at 100V for 1 second and 100 seconds is greater than 0.5.
[0019] The belt according to the second aspect of the present disclosure can achieve high transferability even when a recording medium having large surface irregularities is used, compared with the case where the surface layer contains a resin other than a polyimide resin or a polyamideimide resin.
[0020] The belt according to the third aspect of the present disclosure can achieve high transferability even when a recording medium having large surface irregularities is used, compared with a case where the surface layer contains a resin other than the polyimide resin.
[0021] The belt according to the fourth aspect of the present disclosure can achieve high transferability even when a recording medium having large surface irregularities is used, compared with a case where the surface layer does not contain carbon black.
[0022] The belt according to the fifth aspect of the present disclosure can achieve high transferability even when using a recording medium with large surface irregularities, compared with the case where the amount of carbon black is less than 10 mass % or greater than 22 mass % of the total mass of the surface layer.
[0023] The belt according to the sixth aspect of the present disclosure can achieve high transferability even when a recording medium having large surface irregularities is used, compared with the case where the average primary particle diameter of carbon black is less than 2 nm or greater than 20 nm.
[0024] The belt according to the seventh aspect of the present disclosure can achieve high transferability even when a recording medium having large surface irregularities is used, compared with a case where the total thickness of the belt is less than 60 μm or greater than 120 μm.
[0025] The belt according to the eighth aspect of the present disclosure can achieve high transferability even when a recording medium having large surface irregularities is used, compared with a case where the thickness of the surface layer is more than 50% of the total thickness of the belt.
[0026] Compared with the case where the surface resistivity of the outer peripheral surface of the belt at 100V for 3 seconds is less than 11.0logΩ / sq or greater than 13.5logΩ / sq, the case where the volume resistivity of the belt at 100V for 5 seconds is less than 10.0logΩ·cm or greater than 12.5logΩ·cm, or the case where the difference between the surface resistivity values of the outer peripheral surface of the belt at 100V for 1 second and 100 seconds is greater than 0.5, the intermediate transfer belt according to the tenth aspect of the present invention and the image forming device according to the eleventh aspect of the present invention can achieve high transferability even when using a recording medium with large surface irregularities. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Exemplary embodiments of the present disclosure will be described in detail based on the following drawings, in which:
[0028] Figure 1 is a schematic diagram illustrating an example of an image forming apparatus according to the exemplary embodiment. DETAILED DESCRIPTION
[0029] Exemplary embodiments are described below. The following description and the following examples are intended to illustrate exemplary embodiments and are not intended to limit the scope of exemplary embodiments.
[0030] In an exemplary embodiment, a numerical range expressed using "to" means a range specified by the minimum value and the maximum value described before and after "to", respectively.
[0031] In an exemplary embodiment, when a numerical range is described in a stepwise manner, the upper limit or lower limit of the numerical range can be replaced by the upper limit or lower limit of another numerical range, respectively. In an exemplary embodiment, the upper limit and lower limit of the numerical range can be replaced by the upper limit and lower limit described in the following examples.
[0032] The term "step" used herein refers not only to a single step but also to a step that is indistinguishable from other steps but achieves the intended purpose of the step.
[0033] In the exemplary embodiment, when the exemplary embodiment is described with reference to the drawings, the structure of the exemplary embodiment is not limited to the structure shown in the drawings. The sizes of the components shown in the drawings are conceptual and do not limit the relative relationship between the sizes of the components.
[0034] Each component described in the exemplary embodiment may include multiple types of substances corresponding to the component. In the exemplary embodiment, when the composition includes multiple substances corresponding to the components of the composition, unless otherwise specified, the content of the component in the composition is the total content of the multiple substances in the composition.
[0035] bring
[0036] The inventors of the present disclosure have conducted extensive research on the resistivity of the belt and have discovered that by setting the volume resistivity of the belt and the surface resistivity of the outer peripheral surface of the belt to fall within specific ranges and setting an upper limit on the change in the surface resistivity of the outer peripheral surface of the belt that occurs when the amount of time the voltage is applied is changed, high transferability can be achieved even when using a recording medium with large surface irregularities.
[0037] A belt designed based on the above findings is a belt according to the following exemplary embodiment.
[0038] The belt according to the exemplary embodiment is a belt capable of holding a toner image for an image forming device, the belt including a multilayer structure having a surface layer defining the outer peripheral surface of the belt. The volume resistivity of the belt at 100V for 5 seconds is 10.0 logΩ·cm or more and 12.5 logΩ·cm or less. The surface resistivity of the outer peripheral surface of the belt at 100V for 3 seconds is greater than 11.0 logΩ / sq and less than or equal to 13.5 logΩ / sq. The difference between the surface resistivity of the outer peripheral surface of the belt at 100V for 1 second and the surface resistivity of the outer peripheral surface of the belt at 100V for 100 seconds is 0.5 or less.
[0039] The belt according to the exemplary embodiment can achieve high transferability even when a recording medium having large surface irregularities is used.
[0040] Details of the belt according to the exemplary embodiment are described below.
[0041] The belt according to the exemplary embodiment is a belt used in an image forming apparatus and capable of holding a toner image.
[0042] Examples of the belt capable of holding a toner image include an intermediate transfer belt. The belt according to the exemplary embodiment may be an open belt or an endless belt. The belt according to the exemplary embodiment may be a belt including a surface layer, a base layer, and a layer other than the surface layer or the base layer.
[0043] Volume resistivity
[0044] The tape according to the exemplary embodiment has a 5-second volume resistivity ρv at 100 V of 10.0 logΩ·cm or more and 12.5 logΩ·cm or less.
[0045] The 5-second volume resistivity ρv of the tape at 100 V according to the exemplary embodiment is preferably 11.0 logΩ·cm or more and 12.5 logΩ·cm or less, and more preferably 11.7 logΩ·cm or more and 12.2 logΩ·cm or less.
[0046] The volume resistivity of the tape was determined by the following method.
[0047] Using a microammeter "R8430A" manufactured by Advantest Corporation as a resistance meter and a UR probe manufactured by Mitsubishi Chemical Corporation as a probe, the volume resistivity (logΩ·cm) of the tape was measured at 6 locations spaced at a specified interval in the circumferential direction, at the center and both sides of the tape in the width direction (i.e., a total of 18 locations), wherein the applied voltage was 100V, the voltage application time was 5 seconds, and the pressure was 1 kgf. The average value of the volume resistivity value was calculated. The above measurements were performed at 22°C and 55% RH.
[0048] The term "5-second volume resistivity at 100 V" used herein refers to the volume resistivity of the tape measured after a lapse of 5 seconds from the start of application of a voltage of 100 V.
[0049] Surface resistivity of the outer surface of the belt
[0050] The outer peripheral surface of the belt according to the exemplary embodiment has a 3-second surface resistivity ρs1 at 100 V greater than 11.0 logΩ / sq and less than or equal to 13.5 logΩ / sq.
[0051] The 3-second surface resistivity ρs1 of the outer peripheral surface of the belt at 100 V is preferably 11.5 logΩ / sq or more and 13.5 logΩ / sq or less, and more preferably 12.5 logΩ / sq or more and 13.3 logΩ / sq or less.
[0052] The outer peripheral surface of the belt according to the exemplary embodiment has a difference between surface resistivity values at 1 second and 100 seconds at 100 V, ie, [surface resistivity at 1 second at 100 V] - [surface resistivity at 100 V at 100 seconds] of 0.5 or less.
[0053] The difference in surface resistivity is more preferably 0.3 or less, and may be zero.
[0054] Surface resistivity of the inner surface of the belt
[0055] In order to reduce discharge that may occur on the rear surface of the belt (i.e., the surface of the belt opposite to the outer peripheral surface: the inner peripheral surface) due to charge accumulation on the rear surface of the belt during the transfer process, the 5-second surface resistivity ρs2 of the inner peripheral surface of the belt at 500V according to an exemplary embodiment is preferably greater than 10.5logΩ / sq and less than 13.0logΩ / sq, more preferably greater than 12.0logΩ / sq and less than 13.0logΩ / sq, and further preferably greater than 12.0logΩ / sq and less than 12.7logΩ / sq.
[0056] The surface resistivity of the tape was determined by the following method.
[0057] Using a micro-ammeter "R8430A" manufactured by Advantest Corporation as a resistance meter and a UR probe manufactured by Mitsubishi Chemical Corporation as a probe, the surface resistivity (logΩ / sq) of the belt was measured at 6 positions spaced at a specified interval in the circumferential direction, at the center and both sides of the belt in the width direction (i.e., a total of 18 positions), wherein the applied voltage was 100V or 500V, the voltage application time was 1, 3, 100 seconds, and the pressure was 1kgf. The average value of the surface resistivity value was calculated. The above measurements were performed at 22°C and 55%RH.
[0058] The term "3-second surface resistivity at 100 V" used herein refers to the surface resistivity of the tape measured after 3 seconds have passed since the start of application of a voltage of 100 V. Similarly, the term "1-second surface resistivity at 100 V" used herein refers to the surface resistivity of the tape measured after 1 second has passed since the start of application of a voltage of 100 V, the term "100-second surface resistivity at 100 V" used herein refers to the surface resistivity of the tape measured after 100 seconds have passed since the start of application of a voltage of 100 V, and the term "5-second surface resistivity at 500 V" used herein refers to the surface resistivity of the tape measured after 5 seconds have passed since the start of application of a voltage of 500 V.
[0059] When the UR probe is pressed against the outer circumference of the belt, the surface resistivity ρs1 of the outer circumference of the belt can be measured. Similarly, when the UR probe is pressed against the surface of the belt opposite to the outer circumference (i.e., the inner circumference of the belt), the surface resistivity ρs2 of the inner circumference of the belt can be measured.
[0060] In order to achieve the above-mentioned volume resistivity and surface resistivity of the tape according to the exemplary embodiment, the type of resin contained in the surface layer, the type of conductive agent contained in the surface layer, the particle size thereof, and the amount and ratio of the above-mentioned components can be appropriately selected. The volume resistivity and surface resistivity of the tape can also be controlled by adjusting the distribution of the conductive agent particles in the surface layer.
[0061] In order to easily control the volume resistivity and surface resistivity of the tape, it is also possible to appropriately select the type of resin contained in the base layer arranged adjacent to the surface layer, select the type of conductive agent contained in the base layer, select its particle size, and adjust the amount and ratio of the above components. The volume resistivity and surface resistivity of the tape can also be easily controlled by adjusting the distribution of the conductive agent particles in the base layer.
[0062] Surface layer
[0063] A belt according to an exemplary embodiment includes a surface layer defining an outer circumference of the belt.
[0064] In order to increase the mechanical strength and improve the dispersibility of the conductive agent (e.g., carbon black), the surface layer may include at least one selected from the group consisting of a polyimide resin and a polyamide-imide resin. In particular, in order to increase the dispersibility of carbon black particles (specifically, the dispersibility of carbon black particles with a smaller diameter), the surface layer may include a polyamide-imide resin.
[0065] In order to adjust the resistivity, the surface layer may include a conductive agent. In particular, the surface layer may include carbon black.
[0066] Polyamide-imide resin
[0067] The surface layer may include polyamide-imide resin.
[0068] The polyamideimide resin may be any resin including a repeating unit having an imide bond and an amide bond.
[0069] Specific examples of the polyamideimide resin include polymers prepared by polymerizing a trivalent carboxylic acid compound having an acid anhydride group (ie, tricarboxylic acid) with a diisocyanate or a diamine compound.
[0070] The tricarboxylic acid may be trimellitic anhydride or a derivative of trimellitic anhydride. The tricarboxylic acid may be used in combination with tetracarboxylic dianhydride, aliphatic dicarboxylic acid, aromatic dicarboxylic acid, or the like.
[0071] Examples of the diisocyanate compound include 3,3'-dimethylbiphenyl-4,4'-diisocyanate, 2,2'-dimethylbiphenyl-4,4'-diisocyanate, biphenyl-4,4'-diisocyanate, biphenyl-3,3'-diisocyanate, biphenyl-3,4'-diisocyanate, 3,3'-diethylbiphenyl-4,4'-diisocyanate, 2,2'-diethylbiphenyl-4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, 2,2'-dimethoxybiphenyl-4,4'-diisocyanate, naphthalene-1,5-diisocyanate and naphthalene-2,6-diisocyanate.
[0072] Examples of the diamine compound include compounds having a structure similar to any of the above-described isocyanates and including an amino group instead of an isocyanate group.
[0073] The surface layer may include only one type of polyamideimide resin or two or more types of polyamideimide resins.
[0074] The content of the polyamide-imide resin in the surface layer is not limited and can be set so that the volume resistivity of the belt and the surface resistivity of the outer peripheral surface of the belt fall within the above-mentioned respective predetermined ranges. For example, the content of the polyamide-imide resin in the surface layer is preferably 60% by mass or more and 95% by mass or less of the total mass of the surface layer, more preferably 70% by mass or more and 95% by mass or less, and further preferably 75% by mass or more and 90% by mass or less.
[0075] Carbon Black
[0076] The surface layer may include carbon black.
[0077] Since carbon black has high electrical conductivity, carbon black can improve electrical conductivity to a great extent even when the amount of carbon black used is small.
[0078] Examples of carbon black contained in the surface layer include Ketjen black, oil furnace black, channel black, acetylene black, and surface-oxidized carbon black (hereinafter, referred to as "surface-treated carbon black"). Among them, surface-treated carbon black is preferred in terms of stability of resistance over time.
[0079] The surface-treated carbon black particles can be prepared by attaching a carboxyl group, a quinone group, a lactone group, a hydroxyl group, or the like to the surface of the carbon black particles. Examples of the method for treating the surface of the carbon black particles include an air oxidation method in which the carbon black particles are brought into contact with air in a high-temperature atmosphere to cause a reaction, a method in which the carbon black particles are reacted with nitrogen oxides or ozone at normal temperature (e.g., 22° C.), and a method in which the carbon black particles are subjected to air oxidation in a high-temperature atmosphere and oxidized using ozone at a low temperature.
[0080] In view of the dispersibility and exposure of carbon black particles on the surface, the average primary particle size of the carbon black contained in the surface layer is preferably 2 nm or more and 20 nm or less, and more preferably 5 nm or more and 20 nm or less.
[0081] In exemplary embodiments, the average primary particle size of carbon black is determined by the following method.
[0082] A sample with a thickness of 100 nm was removed from the tape with a slicer. The sample was observed with a transmission electron microscope (TEM). For each of the 50 carbon black particles, the diameter of a circle whose area is equal to the projected area of the carbon black particle was calculated as the size of the carbon black particle. The average value of the sizes of the 50 carbon black particles was regarded as the average primary particle size of the carbon black.
[0083] The surface layer may include only one type of carbon black material or two or more types of carbon black materials.
[0084] The content of carbon black in the surface layer is not limited and can be set so that the volume resistivity of the belt and the surface resistivity of the outer peripheral surface of the belt fall within the above-mentioned respective predetermined ranges. The content of carbon black in the surface layer is preferably 5% by mass or more and 40% by mass or less of the total mass of the surface layer, more preferably 10% by mass or more and 30% by mass or less, and further preferably 10% by mass or more and 22% by mass or less.
[0085] Other Ingredients
[0086] The surface layer may include components other than the above-mentioned components.
[0087] Examples of other components include conductive agents other than carbon black, fillers for increasing the strength of the belt, antioxidants for preventing the belt from being deteriorated by heat, surfactants for improving fluidity, and heat-resistant antioxidants.
[0088] In the case where the surface layer includes other components, the content of other components in the surface layer is preferably greater than 0 mass % and less than or equal to 10 mass %, more preferably greater than 0 mass % and less than or equal to 5 mass %, further preferably greater than 0 mass % and less than or equal to 1 mass %, of the total mass of the surface layer.
[0089] thickness
[0090] In order to increase the ease of production and reduce discharge, the thickness of the surface layer is preferably 1 μm or more and 40 μm or less, and more preferably 3 μm or more and 20 μm or less.
[0091] The thickness of the surface layer is determined by the following method.
[0092] Observe the cross section of the tape in the thickness direction with an optical microscope or a scanning electron microscope. The thickness of the surface layer is measured at 10 locations, and the average value is regarded as the thickness of the surface layer. This method is also applicable to the measurement of the thickness of the substrate layer, as described below.
[0093] Basal layer
[0094] The belt according to the exemplary embodiment has a multilayer structure including a surface layer. The multilayer structure may include a base layer disposed adjacent to the surface layer. The base layer may be a layer defining an inner circumference of the belt.
[0095] In order to increase mechanical strength and improve dispersibility of a conductive agent (eg, carbon black), the base layer may include at least one selected from the group consisting of a polyimide resin and a polyamide-imide resin. In particular, in order to increase mechanical strength, the base layer may include a polyimide resin.
[0096] In order to adjust the resistivity, the base layer may include a conductive agent. In particular, the base layer may include carbon black.
[0097] Polyimide resin
[0098] The base layer may include a polyimide-based resin.
[0099] The polyimide-based resin may be a polyimide resin or a polyamideimide resin, and is preferably a polyimide resin in order to increase mechanical strength.
[0100] Examples of the polyimide resin include a polyimide resin prepared by imidizing a polyamic acid (ie, a precursor of the polyimide resin), which is a polymer prepared by polymerizing a tetracarboxylic dianhydride and a diamine compound.
[0101] Examples of the polyimide resin include resins having a structural unit represented by the following general formula (I).
[0102]
[0103] In the general formula (I), R 1 Represents a tetravalent organic group, R 2 It represents a divalent organic group.
[0104] By R 1 Examples of the tetravalent organic group represented include aromatic groups, aliphatic groups, cyclic aliphatic groups, groups containing aromatic groups and aliphatic groups, and groups formed by substituting the above groups with substituents. Specific examples of the tetravalent organic group include residues of tetracarboxylic dianhydrides described below.
[0105] By R 2 Examples of the divalent organic group represented by include aromatic groups, aliphatic groups, cyclic aliphatic groups, groups containing aromatic groups and aliphatic groups, and groups formed by substituting the above groups with substituents. Specific examples of the divalent organic group include residues of diamine compounds described below.
[0106] Specific examples of the tetracarboxylic dianhydride used as a raw material for the polyimide resin include pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)sulfonic acid dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride and ethylenetetracarboxylic dianhydride.
[0107] Specific examples of the diamine compound used as a raw material for the polyimide resin include 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,3'-dichlorobenzidine, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 1,5-diaminonaphthalene, m-phenylenediamine, p-phenylenediamine, 3,3'-dimethyl-4,4'-biphenylenediamine, benzidine, 3,3'- Dimethylbenzidine, 3,3'-dimethoxybenzidine, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl propane, 2,4-bis(β-amino-tert-butyl)toluene, bis(p-β-amino-tert-butylphenyl) ether, bis(p-β-methyl-δ-aminophenyl)benzene, bis-p-(1,1-dimethyl-5-aminopentyl)benzene, 1-isopropyl-2,4-m-phenylenediamine, m-phenylenediamine, p-phenylenediamine amine, di(p-aminocyclohexyl)methane, hexanediamine, heptanediamine, octanediamine, nonanediamine, decanediamine, diaminopropyltetramethylene, 3-methylheptanediamine, 4,4-dimethylheptanediamine, 2,11-diaminododecane, 1,2-bis-3-aminopropoxyethane, 2,2-dimethylpropylenediamine, 3-methoxyhexanediamine, 2,5-dimethylheptanediamine, 3-methylheptanediamine, 5-methylnonanediamine, 2,17-diamino Aminoeicosane, 1,4-diaminocyclohexane, 1,10-diamino-1,10-dimethyldecane, 12-diaminooctadecane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, piperazine, H2N(CH2)3O(CH2)2O(CH2)NH2, H2N(CH2)3S(CH2)3NH2 and H2N(CH2)3N(CH3)2(CH2)3NH2.
[0108] The base layer may include only one type of polyimide resin or two or more types of polyimide resins.
[0109] In order to reduce discharge and increase the mechanical strength of the belt, the content of the polyimide resin in the base layer is preferably 60 mass % or more and 95 mass % or less, more preferably 70 mass % or more and 95 mass % or less, and further preferably 70 mass % or more and 90 mass % or less of the total mass of the base layer.
[0110] Carbon Black
[0111] In order to, for example, control the number of conductive dots present on the tape according to exemplary embodiments and the volume resistivity of the tape, the base layer may include carbon black.
[0112] The example of the carbon black contained in the base layer comprises Ketjen black, oil furnace black, channel black, acetylene black and surface treated carbon black, which is the same as the example of the carbon black contained in the surface layer. The preferred example of the carbon black contained in the base layer is also the same as the preferred example of the carbon black contained in the surface layer.
[0113] In order to improve dispersibility (especially dispersibility in polyimide resin), increase the mechanical strength of the base layer, and facilitate control of the number of conductive points present on the tape and the volume resistivity of the tape, the average primary particle size of the carbon black contained in the base layer is preferably greater than 20 nm and less than 40 nm, more preferably greater than 20 nm and less than 35 nm, and particularly preferably greater than 20 nm and less than 28 nm.
[0114] The base layer may include only one type of carbon black material or two or more types of carbon black materials.
[0115] In order to improve the dispersibility (especially the dispersibility in polyimide resin), increase the mechanical strength of the base layer, and facilitate the control of the volume resistivity of the belt, the carbon black content in the base layer is preferably greater than 5 mass % and less than 40 mass % of the total mass of the base layer, more preferably greater than 10 mass % and less than 30 mass %, and further preferably greater than 20 mass % and less than 30 mass %.
[0116] Other Ingredients
[0117] The base layer may include components other than the above components.
[0118] Examples of the other components include the same components as those of the surface layer.
[0119] In the case where the base layer includes other components, the content of the other components in the base layer is preferably greater than 0 mass % and less than or equal to 10 mass %, more preferably greater than 0 mass % and less than or equal to 5 mass %, and further preferably greater than 0 mass % and less than or equal to 1 mass %, based on the total mass of the base layer.
[0120] thickness
[0121] In order to increase the mechanical strength of the belt, the thickness of the base layer is preferably 50 μm or more and 100 μm or less, and more preferably 60 μm or more and 80 μm or less.
[0122] Total thickness
[0123] In order to achieve high transferability even when using a recording medium having large surface irregularities, the total thickness of the belt according to the exemplary embodiment is preferably 60 μm or more and 120 μm or less, and more preferably 80 μm or more and 100 μm or less.
[0124] In order to achieve high transferability even when using a recording medium with large surface irregularities, the ratio of the thickness of the surface layer to the total thickness of the belt according to the exemplary embodiment is preferably 3% to 50%, more preferably 3% to 30%, and further preferably 5% to 30%.
[0125] Method for preparing belt
[0126] The method of preparing the tape according to the exemplary embodiment is not limited, and may be any method capable of forming the surface layer and the base layer so that the surface layer and the base layer are adjacent to each other.
[0127] One of the methods of preparing a tape according to an exemplary embodiment is as follows.
[0128] A coating liquid A including carbon black particles dispersed therein and polyamic acid (ie, a precursor of a polyimide resin) dissolved therein was prepared. A coating liquid B including carbon black particles dispersed therein and a polyamideimide resin dissolved therein was also prepared.
[0129] In order to decompose the aggregates of carbon black and improve the dispersibility of carbon black particles, when preparing the coating liquids A and B, a dispersing treatment may be performed using a pulverizer (eg, a jet mill).
[0130] The coating liquid A is applied to the hollow or solid cylinder. The obtained coating film is dried to form a base layer. The coating liquid B is applied to the base layer, and the obtained coating film is dried to form a surface layer.
[0131] The polyamic acid contained in the coating liquid A is imidized after drying the coating film formed by the coating liquid A or after forming the surface layer on the base layer. That is, heating for imidization may be performed after drying the coating film formed by the coating liquid A or after forming the surface layer on the base layer.
[0132] In the heating for imidization, for example, heating is performed at 150° C. to 450° C. (preferably 200° C. to 430° C.) for 20 minutes to 180 minutes (preferably 60 minutes to 150 minutes). This causes an imidization reaction to produce a polyimide.
[0133] The solvent used for preparing the coating liquids A and B is not limited and can be appropriately selected according to the resin to be dissolved in the solvent, etc. For example, the solvent used for preparing the coating liquids A and B may be the following polar solvents.
[0134] Although the base layer is formed by coating in the above method, the base layer may also be formed by the following method:
[0135] A method of preparing pellets comprising a polyimide resin and carbon black and melt-extruding the pellets to form a base layer.
[0136] Examples of polar solvents include N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), hexamethylphosphoramide (HMPA), N-methylcaprolactam, N-acetyl-2-pyrrolidone and 1,3-dimethyl-2-imidazolidinone (N,N-dimethylimidazolidinone, DMI). The above polar solvents can be used alone or in combination of two or more.
[0137] Image forming device
[0138] An image forming apparatus according to the exemplary embodiment includes the belt according to the above-described exemplary embodiment.
[0139] Specifically, the image forming device according to the exemplary embodiment includes: an image holding member; a charging device that charges the surface of the image holding member; an electrostatic latent image forming device that forms an electrostatic latent image on the charged surface of the image holding member; a developing device that includes a developer (including a toner) and uses the developer to develop the electrostatic latent image formed on the surface of the image holding member to form a toner image; a transfer device that transfers the toner image to the surface of a recording medium; and a belt according to the above exemplary embodiment.
[0140] An image forming apparatus according to an exemplary embodiment will be described below with reference to the drawings.
[0141] Figure 1 : is a schematic diagram showing an image forming apparatus according to an exemplary embodiment. An example of the image forming apparatus shown in the figure includes a belt according to an exemplary embodiment used as an intermediate transfer belt.
[0142] By using the belt according to the exemplary embodiment as an intermediate transfer belt, even when a recording medium having large surface irregularities (eg, embossed paper) is used, it is possible to restrict a decrease in transferability and reduce the formation of white spots in concave portions.
[0143] The image forming apparatus 100 according to the exemplary embodiment is, for example, an intermediate transfer image forming apparatus shown in the figure, which is generally referred to as a tandem image forming apparatus. The image forming apparatus 100 includes: a plurality of image forming units 1Y, 1M, 1C, and 1K, which form toner images of yellow (Y), magenta (M), cyan (C), and black (K) by an electrophotographic system; a primary transfer section 10, in which the yellow, magenta, cyan, and black toner images formed by the image forming units 1Y, 1M, 1C, and 1K are sequentially transferred (primary transfer) to an intermediate transfer belt 15; a secondary transfer section 20, in which the superimposed toner images transferred to the intermediate transfer belt 15 are collectively transferred (secondary transfer) to a sheet of paper K as a recording medium; and a fixing device 60, which fixes the image transferred to the sheet of paper K by the secondary transfer to the sheet of paper K. The image forming apparatus 100 also includes a controller 40, which controls the operation of each device and each section.
[0144] Each of the image forming units 1Y, 1M, 1C, and 1K included in the image forming apparatus 100 includes a photosensitive member 11 that rotates in the direction of arrow A and is an example of an image holding member that holds a toner image formed on a surface.
[0145] The photosensitive member 11 is provided with a charger 12 and a laser exposure machine 13 arranged at the periphery of the photosensitive member 11. The charger 12 (an example of a charging unit) charges the photosensitive member 11. The laser exposure machine 13 (an example of a latent image forming unit) writes an electrostatic latent image on the photosensitive member 11 (in the figure, an exposure beam is denoted by Bm).
[0146] The photosensitive member 11 is also provided with a developer 14 and a primary transfer roller 16 arranged at the periphery of the photosensitive member 11. The developer 14 (an example of a developing unit) includes yellow, magenta, cyan, or black toner, and uses the toner to visualize the electrostatic latent image formed on the photosensitive member 11. The primary transfer roller 16 transfers the yellow, magenta, cyan, or black toner image formed on the photosensitive member 11 to the intermediate transfer belt 15 in the primary transfer section 10.
[0147] The photosensitive member 11 is also provided with a photosensitive member cleaner 17 arranged at the periphery of the photosensitive member 11. The photosensitive member cleaner 17 removes toner particles remaining on the photosensitive member 11. The above-mentioned electrophotographic device, that is, the charger 12, the laser exposure machine 13, the developer 14, the primary transfer roller 16, and the photosensitive member cleaner 17 are sequentially arranged at the periphery of the photosensitive member 11 along the rotation direction of the photosensitive member 11. The image forming units 1Y, 1M, 1C, and 1K are arranged substantially linearly in the order of yellow (Y), magenta (M), cyan (C), and black (K) in the rotation direction of the intermediate transfer belt 15.
[0148] The volume resistivity of the intermediate transfer belt 15 used as an intermediate transfer body is, for example, 1×10 6 Ωcm or more and 1×10 14 Ωcm or less, and the thickness is, for example, about 0.1 mm.
[0149] The intermediate transfer belt 15 is driven in a circular manner (i.e., rotated) by various types of rollers at a desired speed in the direction of arrow B shown in the figure. The various types of rollers include: a driving roller 31 that is driven by a high constant speed motor (not shown) and rotates the intermediate transfer belt 15; a supporting roller 32 that supports the intermediate transfer belt 15 extending substantially linearly in the arrangement direction of the photosensitive members 11; a tensioning roller 33 that applies tension to the intermediate transfer belt 15 and serves as a correction roller for preventing the intermediate transfer belt 15 from bending; an idler roller 25 that is provided in the secondary transfer portion 20; and a cleaning idler roller 34 that is provided on a cleaning portion that scrapes off toner particles remaining on the intermediate transfer belt 15.
[0150] The primary transfer section 10 is composed of primary transfer rollers 16 arranged to face the respective photosensitive members 11 across the intermediate transfer belt 15. The primary transfer rollers 16 are arranged to be in pressure contact with the photosensitive members 11, with the intermediate transfer belt 15 interposed therebetween. A voltage (primary transfer bias) having a polarity opposite to the polarity (negative; the same applies hereinafter) of the charged toner particles is supplied to the primary transfer rollers 16. Thus, a transfer electric field is generated in the primary transfer section 10, and the toner images formed on the photosensitive members 11 are electrostatically adsorbed onto the intermediate transfer belt 15 in sequence to form superimposed toner images on the intermediate transfer belt 15.
[0151] The secondary transfer section 20 is constituted by a secondary transfer roller 22 provided on one side of the intermediate transfer belt 15 on which the toner image is held, and a support roller 25 .
[0152] The surface resistivity of the roller 25 is 1×10 7 Ω / sq or more and 1×10 10 Ω / sq or less. The hardness of the support roller 25 is set to, for example, 70° ("ASKER C" produced by KOBUNSHI KEIKI CO., LTD.; the same applies hereinafter). The support roller 25 is provided on the rear surface side of the intermediate transfer belt 15, and serves as a counter electrode of the secondary transfer roller 22. The support roller 25 is provided with a power supply roller 26 made of metal, by which a secondary transfer bias is applied in a stable manner.
[0153] The secondary transfer roller 22 has a volume resistivity of 10 7.5 Ωcm or more and 10 8.5The secondary transfer roller 22 is a hollow cylindrical roller with a diameter of Ωcm or less. The secondary transfer roller 22 is arranged to be in pressure contact with the support roller 25, wherein the intermediate transfer belt 15 is interposed between the secondary transfer roller 22 and the support roller 25. The secondary transfer roller 22 is grounded. A secondary transfer bias is applied between the secondary transfer roller 22 and the support roller 25. Therefore, a transfer electric field is generated in the secondary transfer section 20, and the toner image formed on the intermediate transfer belt 15 is transferred (secondary transfer) to the paper K conveyed to the secondary transfer section 20.
[0154] The intermediate transfer belt cleaner 35 is disposed on the intermediate transfer belt 15 at a position downstream of the secondary transfer section 20 so that the distance between the intermediate transfer belt cleaner 35 and the intermediate transfer belt 15 can be changed. The intermediate transfer belt cleaner 35 removes toner particles and paper dust particles remaining on the intermediate transfer belt 15 after the secondary transfer and cleans the surface of the intermediate transfer belt 15.
[0155] The intermediate transfer belt 15 , the primary transfer section 10 (ie, the primary transfer roller 16 ), and the secondary transfer section 20 (ie, the secondary transfer roller 22 ) correspond to an example of a transfer unit.
[0156] A reference sensor (home position sensor) 42 is provided upstream of the yellow image forming unit 1Y. The reference sensor (home position sensor) 42 generates a reference signal used as a reference to determine the time to form an image in the image forming units 1Y, 1M, 1C, and 1K. An image density sensor 43 is provided downstream of the black image forming unit 1K. The image density sensor 43 is used to adjust the image quality. The reference sensor 42 generates a reference signal when recognizing a mark provided on the back side of the intermediate transfer belt 15. Upon recognizing the reference signal, the controller 40 sends a command to the image forming units 1Y, 1M, 1C, and 1K. Each of the image forming units 1Y, 1M, 1C, and 1K starts forming an image according to the command.
[0157] The image forming apparatus according to the exemplary embodiment further includes the following components as a unit for conveying paper K: a paper tray 50 containing paper K; a paper feed roller 51, which pulls and conveys the paper K stored in the paper tray 50 at a predetermined timing; a conveying roller 52, which conveys the paper K pulled by the paper feed roller 51; a conveying guide device 53, by which the paper K conveyed by the conveying roller 52 is fed into the secondary transfer part 20; a conveying belt 55, which conveys the paper K secondarily transferred by the secondary transfer roller 22 to the fixing device 60; and a fixing inlet guide device 56, by which the paper K is introduced into the fixing device 60.
[0158] A basic process of forming an image using the image forming apparatus according to the exemplary embodiment is described below.
[0159] In the image forming apparatus according to the exemplary embodiment, image data transmitted from an image reading apparatus (not shown) or a personal computer (PC, not shown) or the like is subjected to image processing using an image processing apparatus (not shown), and then the image forming units 1Y, 1M, 1C, and 1K form images.
[0160] In the image processing device, the input reflectivity data is subjected to image processing including various types of image editing (e.g., shading correction, misalignment correction, brightness / color space conversion, gamma correction, frame removal, color editing, and image movement). The image data subjected to image processing is converted into yellow, magenta, cyan, and black colorant gradation data and sent to the laser exposure machine 13.
[0161] The laser exposure machine 13 irradiates the photosensitive member 11 included in each of the image forming units 1Y, 1M, 1C, and 1K with an exposure beam Bm emitted from a semiconductor laser or the like, according to the colorant gradation data received by each laser exposure machine 13. After the surface of the photosensitive member 11 of each of the image forming units 1Y, 1M, 1C, and 1K has been charged by the charger 12, the surface of the photosensitive member 11 is scanned and exposed to the beam by the laser exposure machine 13, and thus, an electrostatic latent image is formed on the surface of the photosensitive member 11. The electrostatic latent image is developed as a Y, M, C, or K toner image in each of the image forming units 1Y, 1M, 1C, and 1K.
[0162] The toner images formed on the photosensitive members 11 of the image forming units 1Y, 1M, 1C, and 1K are transferred to the intermediate transfer belt 15 in the primary transfer section 10, wherein the photosensitive members 11 are in contact with the intermediate transfer belt 15. Specifically, in the primary transfer section 10, the primary transfer roller 16 applies a voltage (primary transfer bias) having a polarity opposite to the polarity (negative) of the charged toner particles to the substrate of the intermediate transfer belt 15 and sequentially superimposes the toner images on the surface of the intermediate transfer belt 15 (primary transfer).
[0163] After the toner images are sequentially transferred (primary transfer) onto the surface of the intermediate transfer belt 15, the intermediate transfer belt 15 is moved and the toner images are conveyed to the secondary transfer section 20. When the toner images are conveyed to the secondary transfer section 20, in the conveying unit, the paper feed roller 51 starts rotating while the toner images are conveyed to the secondary transfer section 20, and a paper K having a desired size is fed from the paper tray 50. The paper K fed by the paper feed roller 51 is conveyed by the conveying roller 52, and reaches the secondary transfer section 20 through the conveying guide 53. Before the paper K reaches the secondary transfer section 20, the feeding of the paper K is suspended, and the alignment between the paper K and the toner images is performed by a registration roller (not shown) that rotates in synchronization with the movement of the intermediate transfer belt 15 on which the toner images are held.
[0164] In the secondary transfer section 20, the secondary transfer roller 22 is pressed by the support roller 25, wherein the intermediate transfer belt 15 is interposed between the secondary transfer roller 22 and the support roller 25. The paper K conveyed to the secondary transfer section 20 at a predetermined time is inserted between the intermediate transfer belt 15 and the secondary transfer roller 22. When a voltage (secondary transfer bias) having the same polarity as the polarity (negative) of the charged toner particles is applied by the power supply roller 26, a transfer electric field is generated between the secondary transfer roller 22 and the support roller 25. The unfixed toner image held on the intermediate transfer belt 15 is electrostatically transferred to the paper K all at once in the secondary transfer section 20 pressurized by the secondary transfer roller 22 and the support roller 25.
[0165] Subsequently, the sheet K to which the toner image has been electrostatically transferred is removed from the intermediate transfer belt 15 and immediately conveyed by the secondary transfer roller 22 to the conveying belt 55, which is located downstream of the secondary transfer roller 22 in the conveying direction of the sheet. The conveying belt 55 conveys the sheet K to the fixing device 60 according to the optimal conveying speed of the fixing device 60. The unfixed toner image present on the sheet K conveyed to the fixing device 60 is fixed to the sheet K by the heat and pressure of the fixing device 60. The sheet K on which the fixed image has been formed is conveyed to a discharge tray (not shown) provided in a discharge portion of the image forming apparatus.
[0166] Toner particles remaining on the intermediate transfer belt 15 after completing the transfer to the paper K are transported to the cleaning portion due to the rotation of the intermediate transfer belt 15 , and are removed from the intermediate transfer belt 15 by the cleaning support roller 34 and the intermediate transfer belt cleaner 35 .
[0167] The exemplary embodiments are described above. It should be understood that the exemplary embodiments described above are not restrictive and that many modifications, variations and improvements may be made to the exemplary embodiments.
[0168] Example
[0169] Examples of the present disclosure are described below. It should be noted that the present disclosure is not limited to the following examples. In the following description, "parts" and "%" are all based on mass.
[0170] Example 1
[0171] Preparation of coating solution A
[0172] Carbon black "SPECIAL Black 4" (average primary particle size: 25 nm) produced by Orion Engineered Carbons was added to an N-methyl-2-pyrrolidone (NMP) solution of a polyamic acid including biphenyltetracarboxylic dianhydride (BPDA) and p-phenylenediamine (PDA) ("U-IMIDE KX" produced by Unitika Ltd., solid content concentration: 20% by mass) so that the ratio of the amount of carbon black to the total solid content in the coating liquid A was 20% by mass or more and 30% by mass or less. The resulting mixture was dispersed with a jet mill disperser "GeanusPY" produced by Geanus (200 N / mm, 2.5 times).
[0173] In order to remove foreign matter and carbon black aggregates, the carbon black dispersed polyamic acid solution was passed through a 20-μm stainless steel mesh. While further stirring the solution, the solution was degassed by vacuum for 15 minutes. Thus, coating liquid A was prepared.
[0174] Preparation of coating solution B
[0175] Carbon black "COLOR BLACK FW1" (average primary particle size: 13 nm) produced by Orion Engineered Carbons was added to a solution of a solvent-soluble polyamide-imide resin (acid value: 8.0 mgKOH / g, solid content concentration: 18% by mass, solvent: N-methyl-2-pyrrolidone) so that the ratio of the amount of carbon black to the total solid content in the coating liquid B was 10% by mass or more and 22% by mass or less. The resulting mixture was dispersed with a jet mill disperser "GeanusPY" produced by Geanus (200 N / mm, 2.5 times).
[0176] In order to remove foreign matter and carbon black aggregates, the carbon black dispersed polyamide-imide resin solution was passed through a 20-μm stainless steel mesh. While further stirring the solution, the solution was degassed by vacuum for 15 minutes. Thus, coating liquid B was prepared.
[0177] Formation of the basal layer
[0178] A hollow cylinder having an outer diameter of 929.5 mm was prepared.
[0179] While the cylinder was rotating, coating liquid A was applied to the outer surface of the cylinder by spiral coating. Subsequently, while the cylinder was kept horizontal, it was dried at 90° C. for 30 minutes. Then, the resulting coating film was heated at 320° C. for 2 hours to form a base layer with a length of 350 mm and a thickness of 75 μm.
[0180] Surface layer formation
[0181] While rotating the cylinder, coating liquid B was applied to the base layer prepared in the above manner by spiral coating. Subsequently, while keeping the cylinder horizontal, it was dried at 90° C. for 30 minutes. Then, the resulting coating film was heated at 260° C. for 2 hours to form a surface layer having a length of 350 mm and a thickness of 5 μm.
[0182] The surface layer and the base layer were removed from the cylinder. Thus, the tape of Example 1 was prepared.
[0183] Examples 2 to 4
[0184] The tapes of Examples 2 to 4 were prepared in the same manner as in Example 1, except that the contents of carbon black in the coating liquids A and B were appropriately changed within the above range.
[0185] Example 5
[0186] The tape of Example 5 was prepared in the same manner as in Example 1, except that the contents of carbon black in the coating liquids A and B were changed within the above range, and the thickness of the base layer was changed to 115 μm.
[0187] Example 6
[0188] The tape of Example 6 was prepared in the same manner as in Example 1, except that the contents of carbon black in the coating liquids A and B were changed within the above ranges, and the thickness of the base layer was changed to 40 μm, and the thickness of the surface layer was changed to 40 μm.
[0189] Example 7
[0190] The tape of Example 7 was prepared in the same manner as in Example 1, except that the contents of carbon black in the coating liquids A and B were changed within the above range, and the thickness of the surface layer was changed to 15 μm.
[0191] Example 8
[0192] A tape of Example 8 was prepared in the same manner as in Example 1, except that a coating liquid C prepared in the following manner was used instead of the coating liquid B to form the surface layer.
[0193] Preparation of coating solution C
[0194] Carbon black "COLOR BLACK FW1" (average primary particle size: 13 nm) produced by Orion Engineered Carbons was added to an N-methyl-2-pyrrolidone (NMP) solution of a polyamic acid including biphenyltetracarboxylic dianhydride (BPDA) and p-phenylenediamine (PDA) ("U-IMIDE KX" produced by Unitika Ltd., solid content concentration: 20% by mass) so that the ratio of the amount of carbon black to the total solid content in the coating liquid C was 10% by mass or more and 22% by mass or less. The resulting mixture was dispersed with a jet mill disperser "GeanusPY" produced by Geanus (200 N / mm, 2.5 times).
[0195] In order to remove foreign matter and carbon black aggregates, the carbon black dispersed polyamic acid solution was passed through a 20-μm stainless steel mesh. While further stirring the solution, the solution was degassed by vacuum for 15 minutes. Thus, a coating liquid C was prepared.
[0196] Comparative Examples 1 to 6
[0197] Tapes of Comparative Examples 1 to 6 were prepared in the same manner as in Example 1, except that the contents of carbon black in the coating liquids A and B were changed within the above range.
[0198] Comparative Example 7
[0199] A tape of Comparative Example 7 was prepared in the same manner as in Example 1, except that the contents of carbon black in the coating liquids A and B were changed within the above range, and the thickness of the base layer was changed to 140 μm.
[0200] Comparative Example 8
[0201] A tape of Comparative Example 8 was prepared in the same manner as in Example 1, except that the contents of carbon black in the coating liquids A and B were changed within the above range, and the thickness of the surface layer was changed to 10 μm.
[0202] Comparative Example 9
[0203] A tape of Comparative Example 9 was prepared in the same manner as in Example 1, except that a coating liquid D prepared in the following manner was used instead of the coating liquid B to form the surface layer.
[0204] Preparation of coating solution D
[0205] Carbon black "SPECIAL Black 4" (average primary particle size: 25 nm) produced by Orion Engineered Carbons was added to a solution of a solvent-soluble polyamide-imide resin (acid value: 8.0 mgKOH / g, solid content concentration: 18% by mass, solvent: N-methyl-2-pyrrolidone) so that the ratio of the amount of carbon black to the total solid content in the coating liquid D was 10% by mass or more and 22% by mass or less. The resulting mixture was dispersed with a jet mill disperser "GeanusPY" produced by Geanus (200 N / mm, 2.5 times).
[0206] In order to remove foreign matter and carbon black aggregates, the carbon black dispersed polyamide-imide resin solution was passed through a 20-μm stainless steel mesh. While further stirring the solution, the solution was degassed by vacuum for 15 minutes. Thus, coating liquid D was prepared.
[0207] Comparative Examples 10 and 11
[0208] The tapes of Comparative Examples 10 and 11 were prepared in the same manner as in Example 1, except that the content of carbon black in coating liquid A was changed within the above-mentioned range, and after changing the content of carbon black in coating liquid A within the above-mentioned range, a base layer with a thickness of 33 μm was formed using coating liquid A, and a surface layer with a thickness of 67 μm was formed on the base layer by using coating liquid A instead of coating liquid B.
[0209] Measurement and evaluation
[0210] The following measurements and evaluations were performed on each of the tapes prepared in Examples.
[0211] Table 1 summarizes the results.
[0212] The volume resistivity and surface resistivity of each tape prepared in the example were measured by the above method. Specifically, the following values (1) to (4) were determined.
[0213] (1) Volume resistivity at 100 V for 5 seconds (expressed as “ρv(100 V, 5 sec)” in Table 1)
[0214] (2) Surface resistivity of the outer surface of the belt at 100 V for 3 seconds (indicated as "ρs1(100 V, 3 sec)" in Table 1)
[0215] (3) The difference in surface resistivity between the outer surface of the belt at 100 V for 1 second and 100 seconds (expressed as "ρs1[100VΔ(100sec-1sec)]" in Table 1)
[0216] (4) Surface resistivity of inner circumferential surface of tape at 500 V for 10 seconds (expressed as “ρs2(500 V, 10 sec)” in Table 1) The thickness of the layers included in each tape prepared in the examples and the total thickness of the tape were also measured by the above method.
[0217] Evaluation of transferability of embossed paper
[0218] The belt prepared in each example was used as an intermediate transfer belt, and the transfer efficiency was evaluated in the following manner.
[0219] The intermediate transfer belt was attached to an "Iridesse (registered trademark) production press" manufactured by Fuji Xerox Co., Ltd., and image quality evaluation was performed.
[0220] In the image quality evaluation, embossed paper "LEATHAC 66" (250 gsm) was used. A black halftone solid image (image density: 60%) was evaluated.
[0221] G1: There are no white spots in the concave areas of the paper.
[0222] G2: There are almost no white spots in the concave areas of the paper.
[0223] G3: There are a few white spots in the concave areas of the paper.
[0224] G4: There are white spots in most of the concave areas of the paper.
[0225] Table 1 summarizes the results.
[0226]
[0227] A detailed description of the abbreviations used in Table 1 is as follows.
[0228] PAI: Polyamide-imide resin
[0229] PI: Polyimide resin
[0230] CB: Carbon Black
[0231] The results in Table 1 confirm that the belt prepared in the example achieves higher transferability than the belt prepared in the comparative example even when a recording medium having large surface irregularities is used.
[0232] The foregoing description of exemplary embodiments of the present disclosure is provided for the purpose of illustration and description. It is not intended to be exhaustive of the precise form disclosed by the present disclosure or to limit the present disclosure to the precise form disclosed. Obviously, many improvements and variations are obvious to those skilled in the art. The embodiments are selected and described in order to best explain the principles of the present disclosure and its practical use, so that other technical personnel in the field can understand the various embodiments and various improvements of the present disclosure suitable for the expected specific use. The scope of the present disclosure is defined by the following claims and their equivalents.
Claims
1. A belt capable of holding a toner image for an image forming device, the belt comprising: a multilayer structure comprising a surface layer defining the outer circumference of the belt, The tape has a 5-second volume resistivity at 100 V of 10.0 log Ω·cm or more and 12.5 log Ω·cm or less, the 5-second volume resistivity at 100 V being measured 5 seconds after the start of application of a voltage of 100 V, The outer peripheral surface of the belt has a surface resistivity of greater than or equal to 12.5 logΩ / sq and less than or equal to 13.5 logΩ / sq at 100V for 3 seconds, the surface resistivity at 100V for 3 seconds being measured after 3 seconds have passed since the start of application of a voltage of 100V, The difference between the surface resistivity of the outer circumference of the belt at 100V for 1 second and the surface resistivity of the outer circumference of the belt at 100V for 100 seconds is 0.5 or less, the surface resistivity for 1 second being measured after 1 second has passed since the start of application of the voltage of 100V, and the surface resistivity for 100 seconds being measured after 100 seconds has passed since the start of application of the voltage of 100V, and The thickness of the surface layer is greater than or equal to 3% and less than or equal to 30% of the total thickness of the belt.
2. The belt according to claim 1, wherein The surface layer includes at least one selected from the group consisting of a polyimide resin and a polyamideimide resin.
3. The belt according to claim 2, wherein: The surface layer is composed of polyimide resin.
4. The belt according to claim 1 or 2, wherein: The surface layer contains carbon black.
5. The belt according to claim 4, wherein The amount of the carbon black is 10% by mass or more and 22% by mass or less of the total mass of the surface layer.
6. The belt according to claim 5, wherein The average primary particle size of the carbon black is 2 nm or more and 20 nm or less.
7. The belt according to any one of claims 1 to 5, wherein The total thickness of the tape is 60 μm or more and 120 μm or less.
8. The belt according to any one of claims 1 to 7, wherein The multi-layer structure includes a substrate layer disposed adjacent to the surface layer.
9. An intermediate transfer belt comprising the belt according to any one of claims 1 to 8. 10 . An image forming apparatus comprising the belt according to claim 1 .
Citation Information
Patent Citations
Annular body, annular body stretching device and image forming apparatus
CN101546164A
Method for determining change in resistance in electric resistance member, and image-forming device using the same
JP2005024392A